Ancestors, kings, and the Dao - Cook, Constance A. (Harvard-Yenching Institute monograph series, 2017)
"Traces the rise of poetry from eulogies in BCE excavated texts and outlines the evolution of musical performance within and away from the context of ancestor worship. Compares the rhetoric of bronze inscriptions with later uses of similar terms in newly discovered bamboo texts from the Warring States period"--